Effectiveness of biomechanically stable pergola-like additively manufactured scaffold for extraskeletal vertical bone augmentation - Yang, Wei; Wang, Chao; Luo, Wenping; Apicella, Antonio; Ji, Ping; Wang, Gong; Liu, Bingshan; Fan, Yubo (Frontiers in Bioengineering and Biotechnology, 2023)
Objective: Extraskeletal vertical bone augmentation in oral implant surgery requires extraosseous regeneration beyond the anatomical contour of the alveolar bone. It is necessary to find a better technical/clinical solution to solve the dilemma of vertical bone augmentation. 3D-printed scaffolds are all oriented to general bone defect repair, but special bone augmentation design still needs improvement. Methods: This study aimed to develop a structural pergola-like scaffold to be loaded with stem cells from the apical papilla (SCAPs), bone morphogenetic protein 9 (BMP9) and vascular endothelial growth factor (VEGF) to verify its bone augmentation ability even under insufficient blood flow supply. Scaffold biomechanical and fluid flow optimization design by finite element analysis (FEA) and computational fluid dynamics (CFD) was performed on pergola-like additive-manufactured scaffolds with various porosity and pore size distributions. The scaffold geometrical configuration showing better biomechanical and fluid dynamics properties was chosen to co-culture for 2 months in subcutaneously into nude mice, with different SCAPs, BMP9, and (or) VEGF combinations. Finally, the samples were removed for Micro-CT and histological analysis. Results: Micro-CT and histological analysis of the explanted scaffolds showed new bone formation in the “Scaffold + SCAPs + BMP9” and the “Scaffold + SCAPs + BMP9 + VEGF” groups where the VEGF addition did not significantly improve osteogenesis. No new bone formation was observed either for the “Blank Scaffold” and the “Scaffold + SCAPs + GFP” group. The results of this study indicate that BMP9 can effectively promote the osteogenic differentiation of SCAPs. Conclusion: The pergola-like scaffold can be used as an effective carrier and support device for new bone regeneration and mineralization in bone tissue engineering, and can play a crucial role in obtaining considerable vertical bone augmentation even under poor blood supply.